2021
DOI: 10.1101/2021.02.10.430452
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing for parallel genomic and epigenomic footprints of adaptation to urban life in a passerine bird

Abstract: Identifying the molecular mechanisms involved in rapid adaptation to novel environments and determining their predictability are central questions in Evolutionary Biology and pressing issues due to rapid global changes. Complementary to genetic responses to selection, faster epigenetic variations such as modifications of DNA methylation may play a substantial role in rapid adaptation. In the context of rampant urbanization, joint examinations of genomic and epigenomic mechanisms are still lacking. Here, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 92 publications
(132 reference statements)
0
6
0
Order By: Relevance
“…An important, remaining question is whether the differences in the circadian properties between city and forest birds observed here are caused by local adaptation of clocks, or are merely a phenotypic response. There is evidence that genetic change can be rapid in cities [6567], and the phenotypic differences between city and forest birds could indeed reflect genetic differences in the response of their clocks to light. However, the high plastic nature of activity patterns and the reversible nature of clock properties (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…An important, remaining question is whether the differences in the circadian properties between city and forest birds observed here are caused by local adaptation of clocks, or are merely a phenotypic response. There is evidence that genetic change can be rapid in cities [6567], and the phenotypic differences between city and forest birds could indeed reflect genetic differences in the response of their clocks to light. However, the high plastic nature of activity patterns and the reversible nature of clock properties (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary ecologists now study epigenetic mechanisms to provide insights into the potential role of epigenetic variation in adaptation to changing environments. To assess the evolutionary implications, DNA methylation has been studied in relation to heritability (Hu et al, 2021;van Oers et al, 2020), whether it might be under selection (Laine et al, 2016;Skinner et al, 2014) and whether it might be involved in range expansion and adaptation (Caizergues et al, 2021;Gore et al, 2018;Heckwolf et al, 2020;Liebl et al, 2013;Meröndun et al, 2019;Riyahi et al, 2017;Schrey et al, 2012;Sheldon et al, 2018).…”
Section: Role Of Epigenetic Variation In Adaptation To Changing Envir...mentioning
confidence: 99%
“…Hence, DNA methylation has become of great interest and, as a result, the number of studies on the causes and consequences of DNA methylation in natural populations is rising. Studies that aim to provide insights into the origin of variation in DNA methylation focus on a wide range of environmental influences, including pH (Massicotte & Angers, 2012), habitat quality (Hu et al, 2019), parasites (Hu et al, 2018; McNew et al, 2021; Wenzel & Piertney, 2014), and anthropogenic causes such as urbanization (Caizergues et al, 2021; Garcia et al, 2019; McNew et al, 2017; Riyahi et al, 2015; Watson et al, 2021) and contaminants (Laine et al, 2021; Mäkinen et al, 2021; McNew et al, 2021; Nilsen et al, 2016; Pierron et al, 2014; Romano et al, 2017). In addition, studies have now included DNA methylation changes as a possible mechanism causing phenotypic changes due to environmental experiences during early development, such as brood size (Sepers et al, 2021; Sheldon et al, 2018), diet or resource availability (Laubach et al, 2019; Lea et al, 2016; Weyrich et al, 2018), predation risk (Noguera & Velando, 2019) and parental effects (Bentz et al, 2016; Rubenstein et al, 2016; Weyrich et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, a few lines of evidence from species with genotypic sex determination support this possibility. Several studies have identified autosomal sex‐associated variation in DNAm patterns across species differing in sex‐determination system in somatic tissues (Gatev et al, 2021 ), including blood (Caizergues et al, 2021 ; Janowitz Koch et al, 2016 ), muscle (Wan et al, 2016 ) and liver (Hu et al, 2019 ; Zhuang et al, 2020 ). Some sex‐biased autosomal DNAm patterns have even been shown to be established during development and stable throughout the life course (Gatev et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%